Devices, subjectivities and mathematics education - Carlos Alberto Garzón (Corporación Universitaria Minuto de Dios, 2014)
A reflection on the relationship between discourse and educational activities with regard to critical mathematics education and the constitution of subjectivities through educational devices arises. The power that is exercised in the teaching of mathematics is evident, especially from school devices with exclusive assessment practices where docile individuals are made of. These practices are part of international policy of standardization.